Religious beliefs, evolutionary psychiatry, and mental health in America: evolutionary threat assessment systems theory - Flannelly, Kevin J. (Religion, spirituality and health: a social scientific approach, 2017)
Introduction -- Part I: The origin of evolutionary ideas in historical and religious context. Greek philosophy, early Christian theology, purpose, and change -- The Reformation and the Enlightenment -- 19th century evolutionary thought before Charles Darwin -- Part II: Charles Darwin's theories of evolution and reactions to them. Charles Darwin's Origin of species -- Reactions to the Darwin's Origin of species -- Darwin's Descent of man and The Expression of emotions -- Reactions to The expression of emotions -- Part III: Evolutionary psychiatry. Brain evolution and emotions -- Fear in the animal and human brain -- Anxiety disorders as evolutionary adaptations -- Other psychiatric disorders as evolutionary adaptations -- Beliefs and psychiatric symptoms -- Evolutionary threat assessment systems theory -- Part IV: Religious beliefs and mental health. Belief in God and life-after-death among American adults -- Religion and death anxiety -- Belief in life-after-death and mental health -- Beliefs about life-after-death and psychiatric symptoms -- Beliefs about the nature of God and mental health -- Beliefs about one's relationship with God and mental health -- Belief in God as an attachment figure and mental health -- Belief in meaning in life and mental health -- Religious doubt and mental health -- Belief in divine forgiveness, evil, and Biblical literalism and mental health -- Part V: Summary, conclusions, and recommendations for future research. The historical development of theories of organic evolution -- Darwin's books about evolution and reactions to them -- Evolutionary psychiatry and ETAS theory -- Belief in life-after-death and mental health -- Beliefs about God and mental health -- Belief in meaning, other religious beliefs, religious doubt, and mental health -- Directions for future research on ETAS theory.